Pengaruh Pembelajaran Self Direct Learning Berbasis Teknologi Informasi Terhadap Hasil Belajar Siswa Pada Materi Struktur Atom di Kelas X SMA Negeri 9 Palu - Ering, Novita Septiani; Mustapa, Kasmudin; Jura, Minarni Rama (Jurnal Akademika Kimia, 2017)
The aim of this study was to investigate the effect of self-direct learning based on information technology toward learning outcomes of students in the structure of atoms material in class X SMA 9 Palu. The population in this study was students of class X academic year 2016/2017. The samples were students (n=26) in the class XA as an experimental class (learning by direct self learning) and students (n=25) in class XC as the control class (learning by the conventional method).The data collection was done using an instrument of test results of studying chemistry at the structure of atoms material is valid. The data testing were using t-test statistical analysis of the two parties with the prerequisite test, the normality and homogeneity test. The data analysis results obtained that an average score of the experimental class = 71.04 and for the control class gained an average = 64.80. Based on the statistical hypothesis testing of test two parties obtained that value tcalculation= 6,50and ttable= 2,00ata = 0,05. In this case, H1was accepted and H0 was rejected because tcalculationÂ was in the rejection area of H0.This shows that there was an effect on differences in learning outcomes of students that were taught by self-direct learning and by the conventional method in the structure of atoms material in class X SMA 9 Palu.